Intracranial Calcification after Probable Disseminated Bacillus Calmette–Guérin Infection in a Child with Severe Combined Immunodeficiency - Eser, Isil; Uyan, Zeynep Seda; Kilic, Suar Caki; Uyur, Emek; Arisoy, Emin Sami; Tezcan, Gulsun; Aydogan, Metin (Journal of Pediatric Infectious Diseases, 2020)
Bacillus Calmette–Guérin (BCG) vaccine is administered to infants in countries with a high prevalence of tuberculosis. Severe combined immunodeficiency (SCID) is one of the most severe forms of primary immunodeficiency disease, rendering patients prone to disseminated BCG infection. Early intensive antimycobacterial treatment and bone marrow transplantation may be lifesaving in patients with BCG infection and SCID. The central nervous system is rarely involved in BCG infection. We report a case of disseminated BCG infection with diffuse intracranial calcification, including periventricular white matter, subcortical area, pons and cerebellar white matter after bone marrow transplantation.
Keywords: severe combined immunodeficiency; disseminated BCG infection; intracranial calcification; central nervous system